IMPLICATION OF HEPATITIS C VIRUS ON DEVELOPING OF RHEUMATIC DISEASES - F.N.Shukurova; M.Sh.Karimov (Scholar Express Journals, 2023)
Hepatitis viruses can cause not only liver damage in the form of acute hepatitis, chronic hepatitis, cirrhosis and hepatocellular carcinoma, but also damage to other organs and systems, and in some cases induce independent diseases. Currently, replication of the hepatitis C virus has been proven in peripheral mononuclear cells and bone marrow cells, mainly in B-lymphocytes, in the myocardium in patients with myocarditis or cardiomyopathy, in the skin, in the epithelium of the ducts of the exocrine glands, and in the vascular endothelium in cryoglobulinemic syndrome. The detection of serological markers of autoimmunity in HCV infection, including some organ-specific autoantibodies, suggests autoimmune mechanisms underlying a number of extrahepatic symptoms. For this reason, it is often considered in differential diagnosis in many areas of clinical medicine. Because the diagnostic, therapeutic strategies and prognosis of rheumatic and HCV-induced diseases can be quite different.
Keywords: HCV; arthritis; rheumatoid arthritis